2005
DOI: 10.1021/jp0546453
|View full text |Cite
|
Sign up to set email alerts
|

Full Configuration Interaction Computer Simulation Study of the Thermodynamic and Kinetic Stability of Hydrated Dielectrons

Abstract: The hydrated electron is a unique solvent-supported state comprised of an excess electron that is confined to a cavity by the surrounding water. Theoretical studies have suggested that two-electron solvent-supported states also can be formed; in particular, simulations indicate that two excess electrons could pair up and occupy a single cavity, forming a so-called hydrated dielectron. Although hydrated dielectrons have not been observed directly by experiment, their existence has been posited to explain the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…302 Although the singlet-state dielectron state appears to be stable with respect to dissociation in MD simulations, thermodynamic integration indicated that the dielectron is thermodynamically unstable. 303 Kinetic stability may, however, be sufficient to allow experimental observation. Simulations suggest scenarios for creating nonequilibrium dielectrons via the capture of a newly injected excess electron by a preexisting hydrated electron.…”
Section: The Dynamics and Reactivity Of The Hydrated Dielectronmentioning
confidence: 99%
“…302 Although the singlet-state dielectron state appears to be stable with respect to dissociation in MD simulations, thermodynamic integration indicated that the dielectron is thermodynamically unstable. 303 Kinetic stability may, however, be sufficient to allow experimental observation. Simulations suggest scenarios for creating nonequilibrium dielectrons via the capture of a newly injected excess electron by a preexisting hydrated electron.…”
Section: The Dynamics and Reactivity Of The Hydrated Dielectronmentioning
confidence: 99%
“…46 We also compare and contrast the behavior of our 2EM sodide in water with previous studies of the hydrated dielectron that used an identical simulation model but without the presence of the Na + core. [52][53][54][55][56] We begin by examining the ground-state electronic structure of this hydrated anion and then explore the relationship between the electronic structure and how this ion is solvated by liquid water. We close this section by investigating the unusual po- larizability of the Na anion and provide a simple interpretation as to why this polarizability can only be properly described if both valence electrons are treated quantum mechanically.…”
Section: The Roles Of Exchange and Correlation In The Equilibriumentioning
confidence: 99%
“…These simulations will also help us to understand alkali anion CTTS dynamics in the limit of a highly polar solvent, providing a connection to the increasing number of ultrafast pump-probe experiments on this anion. [18][19][20][21][22][23][24][25][26][27][28][29][30][34][35][36] Finally, our choice to study the aqueous sodide system also allows us to make connection with recent simulations of the hydrated dielectron ͑two excess electrons solvated in a single water cavity͒ by Larsen and Schwartz [52][53][54][55][56] because aqueous sodide may be envisioned as a hydrated dielectron attached to a positive sodium ion Na + . This provides us a means to explore how the presence of a cationic nucleus alters the relaxation dynamics of the dielectron, so that we can learn something general about the dynamic solvation of aqueous anions.…”
Section: Introductionmentioning
confidence: 99%
“…The solvated dielectron can be understood as a stable species formed by the equilibrium between two interacting electrons and surrounding solvent molecules. At present, the existence of solvated dielectrons or captured EE pairs has been confirmed experimentally and theoretically, and such solvated dielectrons exhibit different structures: single cavity‐shaped F ′ central structure; double cavity structure with a certain spatial distance between two weakly‐bound EEs as a bipolaron; and bipolaron non‐cavity structure . Given that the complicated interaction among two related EEs and solvent cavities, the solvated dielectrons dominate much more important electronic, structural properties, and even unique dynamic behaviors, as observed in magnetism, spintronics, nonlinear optical properties, spin coupling dynamics, and other aspects .…”
Section: Introductionmentioning
confidence: 97%
“…Given that the complicated interaction among two related EEs and solvent cavities, the solvated dielectrons dominate much more important electronic, structural properties, and even unique dynamic behaviors, as observed in magnetism, spintronics, nonlinear optical properties, spin coupling dynamics, and other aspects . Therefore, solvated dielectrons are expected to exhibit more intriguing features and promising applications, which has attracted extensive attention and strong interest in research . Moreover, solvated dielectrons are a bit similar to organic diradicals, and may show different novel coupling modes and properties in different media .…”
Section: Introductionmentioning
confidence: 99%